The Complexity of Village Democracy Problems in Law Number 6 of 2014 Concerning Village - Heryansyah, Despan; Agustian, Tomi; Kalsum, Afif Ummi (JASSP, 2021)
The implementation and institutionalization of democracy with the absence of substantial democratization in the lower level of community does necessarily cause a problem. What it has been becoming a culture and being embraced by people for hundred or even thousand years, would be difficult to be transformed, even though its canalization is in the form of constitution. It may work in the conceptual level yet it may find obstacles in the implementation one. This condition influences the implementation of Village Constitution. The village democracy institutionalization is the focus of this study that covers three forms, they are: the election of village head, the village head election disputes, and term of office of village head. The research method of this study is normative-juridical. The writer initially studied the juridical provisions concerning the three main problems above, and then analyzed the implementation problems in the field. The result of this research showed that the direct election of village heads, village head election disputes done by the regional head, and term of office of the village head office for six (6) years in three periods as it is written on Laws Number. 6 of 2014, causes many problems theoretically as well as philosophically. The result of this study is described descriptively and analytically in the analysis part